Skyrmions with multiple topological charges as orbital angular momentum encoders - Shuhua Guan; Xiaolong Zou; Wenhui Duan (Proceedings of the National Academy of Sciences, 2025)
Magnons carrying intrinsic orbital angular momentum (OAM) hold great potential for orbitronics, optics, and communications, but the generation of such magnons poses great challenges. In this work, we propose that magnons with intrinsic OAM can be induced by antiferromagnetic (AFM) skyrmions with multiple topological charges ( Q ). The proposal is demonstrated in a tetragonal lattice frustrated AFM film, where magnetic anisotropy governs the formation of multiple- Q skyrmions. Out-of-plane polarized current induces ultrafast skyrmion helicity oscillation, which enables excitation of multipolar spin waves, with OAM quantum number identical to Q . The Q , and thus OAM, can be modulated by tuning magnetic anisotropy and temperature. In addition, we reveal an unexpected AFM skyrmion Hall effect driven by in-plane polarized current, and a nonlinear correction term in skyrmion dynamics induced by spin–orbit torque fluctuation. Our results reveal unique behaviors of AFM multiple- Q skyrmions and could extend their applications in information encoding and transmission.